On the optimality of activist policies with a less informed government - Jean-Pascal Bénassy (Deutsches Institut für Wirtschaftsforschung (DIW), 1999)
We investigate whether a government should lead an activist policy in a rigorous utility maximizing framework under rational expectations. The economy is a monetary one with preset wages, and is subject to both demand and supply shocks. It is assumed that the government can never act on the basis of information superior to that of the private sector. Morecover wages are set after monetary injections have been carried out. We find that the optimal policy is nevertheless an activist countercyclical one. It has the remarkable property that, although the economy is hit each period by stochastic shocks after wages have been preset, this optimal policy will nevertheless succeed in keeping the economy on a full employment track.
Keywords: 330; Geldpolitik; Unvollkommene Information; Policy-mix; Eigeninteresse; Rationale Erwartung; Geldmengensteuerung; Antizyklische Finanzpolitik; Theorie